The praised and the virgin - Mahmutćehajić, Rusmir, 1948- (Philosophy of Religion - World Religions, 2015)
In The Praised and the Virgin , Rusmir Mahmutćehajić provides an extended theologically and philosophically informed meditation on relations between the Muslim and Christian traditions, through the persons of Muhammad (the Praised) and Mary (the Virgin), as complementary bearers of God's Word. He traces their presence in the extended encounter of the Abrahamic traditions that is Bosnia's past and present, demonstrating how these traditions inform each other, while simultaneously preserving their difference and uniqueness. He lays fundamental groundwork for a more authentic dialogue, based on identity and difference in history under God, that is also a critique of inhumane ideologies and a modernity that has forsaken God and Man, again as reflected in the historical experiences of the Bosnian people.